Adoption of green areas as a space for skills development: A case study - Torres Matos, Leonor; Esteban-Rivera, Edwin Roger; Rojas-Cotrina, Amancio Ricardo (Journal of the University of Zulia, 2022)
Initial Education is the first level of the Peruvian educational system and seeks the integral formation of students, for this reason the community of the Educational Institution "Luis Enrique XIX" of San Martín de Porres, Lima, Peru, adopted an abandoned park which served as a lair to people of bad living, so that students develop skills included in the national curricular design. The purpose of the article is to interpret the process of adopting green areas as a space for the development of the competence of democratic coexistence and inquiry, in students of the Luis Enrique XIX Educational Institution. The case study method, qualitative methodological perspective was used and some information was collected through documentary review, observation and in-depth interview. The project implemented in the educational institution managed to improve democratic coexistence, care for the environment (with agroecological criteria), promoted student inquiry and teacher professionalization.